2017
DOI: 10.1536/ihj.16-104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Atrial Tachyarrhythmias in Patients With Early Repolarization Syndrome

Abstract: SummaryAtrial tachyarrhythmias (ATAs) occur in a significant proportion of Brugada syndrome (BrS) patients and are often an important cause of inappropriate shocks. The aim of this retrospective study was to evaluate the incidence of ATAs and ATA-induced inappropriate shocks in early repolarization syndrome (ERS) patients as compared to BrS patients.We analyzed data from 20 consecutive patients who were diagnosed with ERS and compared them with patients diagnosed with BrS (n = 31). Clinical and ICD interrogati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Besides, we found three patients (18.8%) present with AF, a higher prevalence than in the general population. Watanabe et al reported that AF is found in 23% of their cases with ERS, and AF has been reported in 15% of ERS patients in the investigation of Hwang et al and 22% in the research of Kamakura et al, implying high overlapping between AF and ERS (29)(30)(31). A report also demonstrates that ERP is more common in patients younger than 60 years with lone AF than healthy controls and declares that ERP may indicate susceptibility to AF (32).…”
Section: Discussionmentioning
confidence: 96%
“…Besides, we found three patients (18.8%) present with AF, a higher prevalence than in the general population. Watanabe et al reported that AF is found in 23% of their cases with ERS, and AF has been reported in 15% of ERS patients in the investigation of Hwang et al and 22% in the research of Kamakura et al, implying high overlapping between AF and ERS (29)(30)(31). A report also demonstrates that ERP is more common in patients younger than 60 years with lone AF than healthy controls and declares that ERP may indicate susceptibility to AF (32).…”
Section: Discussionmentioning
confidence: 96%
“…Several ERS cases who survived from an aborted death or VF have been reported. 15) However, to the best of our knowledge, there have been no reports in which the detailed and serial changes in the J-wave amplitude and morphology during therapeutic hypothermia and occurrences of VF were recorded. Therapeutic hypothermia can lead to VF due to an exacerbation of J-waves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several genetic mutations detected in individuals with ERP may also be associated with AF (21,22). These mutations expressed in both atria and ventricles may cause increased susceptibility to AF in addition to the phenotypic expression of ERP (23). Another example for the relationship between ERP and AF is the athlete's heart.…”
Section: Discussionmentioning
confidence: 99%